15. Jika f(x) =5ˣ dan g(x) = x2 + 3 untuk x≠0 maka f⁻¹ (g(x2 )-3) =…….

Posted on

a. 5 log (x2 +3)
b. 5 log (x4 -3)
c. 5 log (x4 +3)
d. 4 5 log x
e. 2 5 log x

15. Jika f(x) =5ˣ dan g(x) = x2 + 3 untuk x≠0 maka f⁻¹ (g(x2 )-3) =…….

Tentukan fungsi dalamnya:

$begin{align}g(x)&=x^2+3 \ g(x^2)&=(x^2)^2+3 \ g(x^2)&=x^4+3 \ g(x^2)-3&=(x^4+3)-3 \ g(x^2)-3&=x^4end{align}

Maka:

$begin{align}fbig(g(x^2)-3)big)&=5^{g(x^2)-3} \ &=5^{x^4}end{align}

Dengan fungsi invers:

$begin{align}y&=5^{x^4} \ x^4&=,^5log y \ x&=sqrt[4]{^5log y}end{align}

Diperoleh:

f^{-1}big(g(x^2)-3)big)=sqrt[4]{^5log x}